Profile of Early Childhood Religious Feeling in Islam-Based Schools - Azzahra Zulaikha; Yuli Kurniawati Sugiyo Pranoto (Ta'dib, 2024)
This study aims to understanding the origins of religious feelings in early childhood, specifically in children aged 5-6 years who attend Islamic-based schools. This research method is qualitative descriptive research. The number of respondents is 33 children from 3 different schools, namely two Integrated Islamic Schools (IT) and one RA (Raudatul Athfal). Data collection was carried out through image-based interviews. (worship practices and emotional expressions). The research results show that most children engage in religious activities because they believe that after worshiping, they will receive goodness. (rewards). What children like the most is praying and reading the Quran. The most commonly chosen emotional expression is being very happy and joyful while engaging in their favorite worship activities.